Senifle Macular Degeneration With Subretinal Neovascularization - Moestidjab, -
"The Patient With Choroidal Neovascularization Usually Notices A Gradual Blurring Of Vision Caused By The Overlying Retinal Edema And Occasional Eudate Formation. However, A Sudden Loss Of Vision Can Becaused By A Hemorrhage Oeneath The Sensory Retina In The Macular Region. During The Earliest Stage Of Choroidal Neovascu- Larization Into The Sub Retinal Pigment Epithelial Space, Neither Funduscopic Examination Nor Fluorescein Anoiography Reveal The First Buds Of Choroidal Capillaries. Early Choroidal Filling And During The Arteriovenous Phase May Portray The Choroidal Neovascu¬Lar Membrane As A Spoked Wheel Or.As A Sea Fan Pattern Of Fluores¬Cence. Laser Phot000Agulation Proper Should Be Selected For Treat¬Ment This Condition And This Selection Depends On The Region Of The Retina And Chorioretinal Structure Affected By The Neovascu¬Lerization. Full-Energy Intensity Photdcoaoulation With Minimal Destruction Of The Retina Can Complete Obliterate The Choroidal Neovascular Membrane. It Is Possible That The Krypton Red Laser Prove Superior To Blue/Green Argon Laser Because Has Less Effect On The Inner Retinal Layer And Penetrates More Deeply In To The Choroidal Neovascularization."